Respostas
respondido por:
0
a) C = K- 273
C = 283 - 273
C = 10°
b ) ( F - 32 ) / 9 = (K - 273) /5
( 42 - 32 ) / 9 = ( K - 273 ) / 5
10 / 9 = ( K - 273 ) / 5
9 • ( k - 273 ) = 10• 5
9K - 2457 = 50
9K = 2457 + 50
9K = 2507
K=2507 / 9
K =278, 5 k
C = 283 - 273
C = 10°
b ) ( F - 32 ) / 9 = (K - 273) /5
( 42 - 32 ) / 9 = ( K - 273 ) / 5
10 / 9 = ( K - 273 ) / 5
9 • ( k - 273 ) = 10• 5
9K - 2457 = 50
9K = 2457 + 50
9K = 2507
K=2507 / 9
K =278, 5 k
respondido por:
0
a)
Tc = Tk - 273
Tc = 283 - 273
Tc = 10
b)
(Tf - 32)/9 = (Tk - 273)/5
(42 - 32)/9 = (Tk - 273)/5
10/9 = (Tk - 273)/5
1,11 = (Tk - 273)/5
Tk - 273 = 5,55
Tk = 273 + 5,55
Tk = 278,55
Perguntas similares
6 anos atrás
6 anos atrás
8 anos atrás
8 anos atrás
9 anos atrás